Design of Low-Profile Frequency-Selective Rasorbers Based on Three-Legged Loaded Element - Yu Qiang; Dongfang Zhou; Qikun Liu; Zhenning Yao (International Journal of Antennas and Propagation)
A novel low-profile dual-polarization frequency-selective rasorber (FSR) with a transmissive window in the absorption band is proposed in this paper. Based on the equivalent circuit model (ECM), the principles of the impedance design are theoretically derived. Then, a two-layer structure model is constructed. The top layer is composed of a lossy three-legged loaded element (TLLE), and the bottom layer is composed of a square ring bandpass frequency-selective surface (FSS). Furthermore, the strips are folded to reduce the unit cell size to stabilize the angular response. The maximum stable response angle increases from 20 to 40° due to the miniaturized design under both TE and TM polarization. The experimental results of the prototype are in good agreement with the simulation results, which validates the rationality of our design.